Using Critical Thinking Styles to Inform Food Safety Behavior Communication Campaigns - Arthur Leal; Joy N. Rumble; Alexa J. Lamm (Journal of Applied Communications, 2017)
Consumers have struggled with maintaining consistent food safety behaviors over the years, which has been affected partly by their limited food safety knowledge. Researchers in this study set to determine Florida residents’ food safety behaviors while also assessing their critical thinking styles. The social cognitive theory and the University of Florida critical thinking styles (UFCTI) inventory served as the guiding framework. The UFCTI has emerged as an effective tool in measuring how an individual’s critical thinking is expressed, performed, or done. Online survey responses were collected from 510 Florida residents and data were analyzed using non-probability and weighting measures. The majority of respondents washed their fresh fruits and vegetables before eating and washed their hands before food preparation. However, respondents were not as likely to disinfect their countertops before food preparation. Respondents exhibited infrequent food label reading behaviors, as well. When receiving food related information, seekers of information preferred printed fact sheets, bulletins or brochures, and demonstration or displays. Whereas, engagers preferred websites. Recommendations included developing communication efforts focused on personalized messages and targeted mediums centered around each critical thinking style. Food safety communication should emphasize the importance and risks of not reading food labels and cleaning countertops. Future research should determine how each critical thinking style uses the mediums where no significant difference was established. Research efforts should focus on expanding the UFCTI and assessing the contributions the social cognitive theory can add.
Keywords: Communication; Critical Thinking; Critical Thinking Styles; Food Safety; Social Cognitive Theory